Anthropometric and fitness characteristics of international, professional and amateur male graduate soccer players from an elite youth academy - le Gall, F.; Carling, C.; Williams, M.; Reilly, T. (Journal of Science and Medicine in Sport, 2010)
We compared anthropometric and fitness performance data from graduate male youth players from an elite soccer academy who on leaving the institution were either successful or not in progressing to higher standards of play. Altogether, 161 players were grouped according to whether they achieved international or professional status or remained amateur. Measures were taken across three age categories (under 14, 15 and 16 years of age). Players were assessed using standard measures of anthropometric and fitness characteristics. The skeletal age of players was also measured to determine maturity status. Multivariate analysis (MANCOVA) identified a significant (p < 0.001) effect for playing status. Univariate analysis revealed a significant difference in maturity status in amateurs and professionals versus internationals (p < 0.05), in body mass in professionals versus amateurs (d = 0.56, p < 0.05), in height (d = 0.85, p < 0.01) and maximal anaerobic power (d = 0.79, p < 0.01) in both professionals and internationals versus amateurs. There was also a significant difference in counter-movement jump (d = 0.53, p < 0.05) and 40-m sprint time (d = 0.50, p < 0.05) in internationals versus amateurs, as well as a significant main effect for age and playing position (p < 0.001). Significant differences were reported for maturity status, body mass, height, peak concentric torque, maximal anaerobic power, and sprint and jump performance with results dependant on age category and playing position. These results suggest that anthropometric and fitness assessments of elite youth soccer players can play a part in determining their chances of proceeding to higher achievement levels.